2014
DOI: 10.1021/ef501694s
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Addition Reactions during Low-Temperature Autoxidation of Oilsands Bitumen

Abstract: Low-temperature oxidation of bitumen with air in the temperature range of 130−160°C was investigated. Of particular interest were the addition reactions taking place during oxidation, which contributed to the observed increase in viscosity of oxidized bitumen. During the autoxidation of bitumen, the relative aliphatic to aromatic loss-ratio of hydrogen increased from 18:1 to 30:1 when the temperature was increased from 140°C to 150°C and then remained almost the same at 160°C. It coincided with a bitumen oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 24 publications
0
64
0
Order By: Relevance
“…8 The GC-MS analyses were performed using an Agilent 78820A GC coupled with an Agilent 5977E mass spectrometer. The products were separated on an HP-5 30 m × 0.25 mm × 0.25 μm column.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The GC-MS analyses were performed using an Agilent 78820A GC coupled with an Agilent 5977E mass spectrometer. The products were separated on an HP-5 30 m × 0.25 mm × 0.25 μm column.…”
Section: Methodsmentioning
confidence: 99%
“…A systematic study of hydrocarbon addition reactions was performed, 8 which confirmed the formation of addition products and the particularly deleterious impact of molecules containing five-membered aliphatic rings. However, oilsands bitumen does not consist of just hydrocarbons; it also contains sulfur, nitrogen, and oxygen.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…2, 3, 4). Oxidation may also give rise to addition reactions [19], particularly in materials that are rich in naphtheno-aromatics, such as the asphaltenes feed. Thus, the polarity, solubility parameter and molecular mass of the molecules were likely increased by oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…5,13,14 Secondary oxidation products (oxidized multiple times), and in some cases addition products (dimerized/ oligomerized), are also generated. 15 Oxidation proceeds via a free radical mechanism, which is well studied and reviewed in literature. 5,13,14 Alkyl free radicals (R˙) are formed (initiation) during the induction period, but initiation has no appreciable effect on product selectivity.…”
Section: Introductionmentioning
confidence: 99%